FREQUENCY AND COMPLICATION OF SERUM IRON OVERLOAD IN TRANSFUSION DEPENDENT PATIENT - Wajeeha Rahman; Ansa kalsoom rehman; Hira arooj; Gulshan munir; Seema gul hussain; Aftab Nazir; Farhana jabeen shah (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: The aim of the current study was to determine the frequency and complications of serum iron overload in transfusion-dependent patients with an aim to assess the prevalence of iron overload and identify associated complications.Methods: The current study adopted cross-sectional and observational research design. The data was collected the transfusion-dependent patients who were receiving regular treatment at the Hayatabad Medical Complex (HMC), Peshawar. A sample of 151 patients who were dependent on transfusion was collected through convenient sampling technique. Information on the duration and frequency of blood transfusions, the frequency of serum ferritin level monitoring, and recent ferritin levels, and complications experienced by the patient due to iron overload were collected through structured questionnaire. Statistical analysis, including demographic, descriptive, chi-square and cross-tabulation was conducted through SPSS.Results: The analysis of 151 transfusion-dependent patients revealed that liver enlargement (29.8%) and fatigue (23.2%) are the most common complications of iron overload. Results also shows that majority of patients (43.0%) have moderate serum iron overload while iron Chelation Therapy is the most commonly administered treatment, particularly for patients with severe iron overload (75%). Patients generally start experiencing complications between 10 and 30 years of age. The demographic data indicate a predominance of thalassemia and a fairly balanced gender distribution among the study participants.Conclusion: Regular monitoring of serum ferritin levels and related issues is crucial for early diagnosis and treatment. Patients need to be educated about the risks of iron overload and the need of sticking to their treatment plans.